Potensi Tumbuhan Sayur sebagai Sumber Pangan Berkelanjutan : Kajian Etnobotani di Desa Ngabab Kabupaten Malang - Chita Aura Suko Nisrinadevi; Retno Ayu Saraswati; Dayinta Rombe Paembonan; Fahrul Ghani Muhaimin; Anas Bagaskara Witanto; Ayu Chandra Mustikasari; Nafi’ Windy Kharisma; Syifa Nabila Firdausya; Heni Refdiana; Susriyati Mahanal (Biocaster : Jurnal Kajian Biologi, 2026)
Changes in community consumption patterns that tend to reduce the use of local vegetables, so that ethnobotanical studies are needed to document and analyze their potential as a sustainable food source. This study aims to identify the diversity and utilization of local vegetables, as well as analyze the ethnobotanical index based on the knowledge of the Ngabab Village community. This study uses a mixed methods approach with an exploratory sequential design. Data were collected through interviews, observations, documentation, and surveys. The determination of informants and respondents was done purposively. Data analysis was carried out qualitatively using the Miles and Huberman model, and quantitatively using the ethnobotanical index. The results showed that there were 11 local vegetable species from 5 families utilized by the community. The Informant Consensus Factor (ICF) value was 0.98, the RFC value showed the highest result of 0.93 in Brassica oleracea (cabbage) which indicates that this species is the vegetable most utilized by the community. In addition, the highest SUV value was also found in Brassica oleracea at 2.12 which indicates the most dominant level of use compared to other species. The Brassicaceae family had the highest FUV value of 1.41, and the most widely utilized part (PPUV) was the fruit (33.03%). The conclusion of this study is that local vegetables play a vital role in the community's food system and have the potential to support food security and the sustainable preservation of local knowledge.